Proceedings of the SIGCHI Conference on Human Factors in Computing Systems Wings for the Mind - CHI '89 1989
DOI: 10.1145/67449.67515
|View full text |Cite
|
Sign up to set email alerts
|

An experiment into the use of auditory cues to reduce visual workload

Abstract: The potential utility of dividing the information flowing from computer to human among several sensory modalitles is investigated by means of a rigorous experiment which compares the effectiveness of auditory and visual cues in the performance of a visual search task. The results indicate that a complex auditory cue can be used to replace cues traditionally presented in the visual modality. Implications for the design of multlmodal workstations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Indeed, Wickens' [2002] description of multiple resources makes theoretical predictions that suggest less dual task interference when information can be spread across modalities rather than processed within a single modality (e.g., by vision alone). Studies have confirmed that auditory displays can be beneficial in scenarios where the display is small [Brewster 2002;Brewster and Murray 2000] or when the display is such that vision may be overtaxed [Brewster 1997;M. L. Brown et al 1989].…”
Section: Rationale: the Need For Auditory Graphsmentioning
confidence: 95%
“…Indeed, Wickens' [2002] description of multiple resources makes theoretical predictions that suggest less dual task interference when information can be spread across modalities rather than processed within a single modality (e.g., by vision alone). Studies have confirmed that auditory displays can be beneficial in scenarios where the display is small [Brewster 2002;Brewster and Murray 2000] or when the display is such that vision may be overtaxed [Brewster 1997;M. L. Brown et al 1989].…”
Section: Rationale: the Need For Auditory Graphsmentioning
confidence: 95%
“…Surveys have shown good support for enhanced visualization and communication, circumscribed thinking -when the designer's ideas are circumscribed by the CAD tool's abilities -and for premature design fixation (premature commitment to a given design solution) [5]. Other studies went one step further and investigated how to reduce the visual cluttering through the use of auditory cues [6], an interesting approach that is currently outside of our scope, but that could be considered in the future.…”
Section: Related Workmentioning
confidence: 99%
“…Spatial audio is perceptible even when the source is off-screen [44], and research has shown its effectiveness in aiding visual search [19] and video conferencing [7]. 3D spatial rendering is implemented in the server by transforming the user's single channel microphone audio stream using an off-the-shelf higher-order ambisonics audio library [100].…”
Section: Viewport Visualizationmentioning
confidence: 99%